The Influence of Organizational Climate on Individual Creativity and Individual Innovative Behavior in Healthcare Settings - Yoga Brahmanda Ariarta, Putu Agus; Surya Putra , Made; Artha Wibawa , I Made; Ketut Surya , Ida Bagus (Journal Research of Social Science, Economics, and Management, 2024)
The study aims to investigate the influence of organizational climate (OC) on individual innovative behavior (IIB) and examine the role of individual creativity (IC) as mediation in the concstruction of proposed relationships. This study involved 88 healthcare worker at Klungkung General Hospital. Data were collected using a 5-point Likert scale. The sampling method employed was non-probability based predefined criteria. Data analysis was done through a structural equation moedel (SEM) using Smart-PLS. The result indicate that OC and IC positively and significantly impact IIB. Additionaly, OC has a positive and significant impact on IC. Meanwhlie, IC acted as a partial mediation in the relationship between OC on IIB. Research on the impact of organizational climate on individual creativity and individual innovative behavior has primarily centered around the private sector. However, the organizational climate within public service entities, especially in healthcare, remains relatively unexplored. This presents a significant knowledge gap that merits further investigation. This research serves as a reference for formulating policy recommendations by hospital management regarding policies aimed at promoting an organizational climate that supports individual creativity and individual innovative behavior.